Pharmacological and Biochemical Aspects of the Lamiaceae Family used in the Treatment of Intestinal Parasitosis in West and Central Africa - Degla, Lissette Houedénou; Olounlade, Pascal Abiodoun; Amoussa, Abdou Madjid Olatoundé; Azando, Erick Virgile Bertrand; Hounzangbe-Adote, Mawule Sylvie; Lagnika, Latifou (Pharmacognosy Reviews)
Background: In the search for new molecules likely to treat intestinal parasitosis with less risk in the short, medium and long term, the potential of medicinal plants is explored. and Ocimum gratissimum are two species of the Lamiaceae family used by populations of intestinal parasitosis from Benin. The aim of this work is to make a bibliographic synthesis of these two species in order to orient research for their use in the control of intestinal parasitosis. Results and Conclusion: H. suaveolens and O. gratissimum are endowed with nutrients, mineral compounds and secondary metabolites (flavonoids, alkaloids, tannins, phenolic compounds, saponins, steroids, glycosides, and essential oils). Antibacterial, antifungal, antioxidant, antiparasitic, antidiabetic, anticancer, antiulcer, wound healing and insecticidal activities are reported. The antimicrobial activities that are reported for H. suaveolens and O. gratissimum may justify their uses in the treatment of gastrointestinal disorders. The gastrointestinal disorders are manifestations but not specific of intestinal parasitosis. However, few studies have investigated the anthelmintic activities of these two species. A strong variation was also noted in the essential oils composition of H. suaveolens and O. gratissimum. This variation is the consequence of several chemotypes of essential oils which can influence the biological activities of the species. Further investigations are therefore important for the use of H. suaveolens and O. gratissimum in the control of intestinal parasitosis.
Keywords: Anthelmintics; Essential oil; Hyptis suaveolens; Intestinal parasites Ocimum gratissimum; Africa.